THE PREFERENCES AND REQUIREMENTS OF GREEN GARDEN RETIREMENT CARE OF THE ELDERLY: CASE STUDY AT RSK TAIPING, PERAK, MALAYSIA - Wan Ali@Yaacob, Wan Noor Anira; Mohd Hussain, Nur Huzeima; Mat Nayan, Nadiyanti; Abdullah, Marina; Teh, Mohd Zulhaili (PLANNING MALAYSIA, 2022)
The elderly people in retirement homes generally pain from health’s problems, depression, and anxiety. Previous study revealed that the elderly requires high consumption of healthcare facilities. However, in Malaysia, the gap of the built environment for green garden, especially in the existing strategy at planning, design, and implementation of the elderly institutional care is currently lacking and inadequate. Consequently, the elderly usually requires much green or naturals to spend considerable time gardening and therapeutic activities. The green garden can entail and develop their stimulation, increase socialization, and decrease feel of isolation. Therefore, this study investigates the requirements of green garden retirement care for the elderly in supporting their active ageing and preferences design of green garden to improve the quality of life at retirement homes. This study embedded mixed-method designs, including structured interviews with the sixteen (16) residents and four (4) staff at RSK Taiping, Perak. together with observation of senior outdoor survey (SOS) tools. Findings revealed that the requirement of green garden retirement care facilities and location influenced garden usage in the elderly at retirement homes. The design considerations of landscape design on green gardens have been identified to be prominent in preferences for the elderly at retirement homes. The evidence in this study is particularly compelling for the holistic planning, design of the green garden at retirement homes and provides better reflection in future policy for institutional care facilities development.